Acid Tolerant and Acidophilic Microalgae: An Underexplored World of Biotechnological Opportunities - Abiusi, Fabian; Trompetter, Egbert; Pollio, Antonino; Wijffels, Rene H.; Janssen, Marcel (Frontiers in Microbiology, 2022)
Despite their large number and diversity, microalgae from only four genera are currently cultivated at large-scale. Three of those share common characteristics: they are cultivated mainly autotrophically and are extremophiles or tolerate “extreme conditions”. Extreme growth conditions aid in preventing contamination and predation of microalgae, therefore facilitating their outdoor cultivation. In search for new algae suitable for large-scale production, we investigated six microalgal strains belonging to four genera and able to grow at pH below 3; reportedly acid tolerant Stichococcus bacillaris ACUF158, Chlamydomonas acidophila SAG 2045, Chlamydomonas pitschmannii ACUF238 and Viridiella fridericiana ACUF035 and acidophilic Galdieria sulphuraria ACUF064 and ACUF074. All strains were cultivated autotrophically at light intensity of 100 and 300 µmol·m-2·s-1 and pH between 1.7 and 2.9. The autotrophic biomass productivities were compared with one of the most productive microalgae, neutrophilic Chlorella sorokiniana SAG 211-8K, grown at pH 6.8. The acid tolerant strains have their autotrophic biomass productivities reported for the first time. Mixotrophic and heterotrophic properties were also investigated when possible. Five of the tested strains showed an autotrophic biomass productivity 10 to 39% lower than C. sorokiniana but comparable with other commercially relevant mesophilic microalgae, indicating the potential of these microalgae for autotrophic biomass production under acidic growing conditions. Two acid tolerant species cultivated mixotrophically with glucose displayed a growth rate higher than the corresponding autotrophic culture. C. acidophila SAG 2045, and the two Galdieria strains were also cultivated heterotrophically with glucose at various temperatures. C. acidophila SAG 2045 failed to grow at 37°C, G. sulphuraria ACUF64 showed a temperature optimum of 37°C while G. sulphuraria ACUF74 of 42°C. For each strain the biomass yield on glucose decreased when it was cultivated above its optimal temperature. The possible biotechnological applications of our findings will be addressed.